The Role of Congress in Advancing Civil Rights: Lessons from Two Movements - Sawyer, Heather (Columbia Journal of Gender and Law, 2015)
It’s wonderful to be here today. This is an exciting time in the marriage equality movement. Just yesterday a Texas judge struck down that state’s ban on marriage between same-sex couples. This comes on the heels of Virginia’s and Oregon’s Attorneys General announcing that they will not defend their state’s anti-marriage laws.